Diversity in software development teams: the moderating effects of interdependence, team tenure and project type. (1st January 2011) - Dyaram, Lata; Kamalanabhan, T.J.
Organisations are increasingly using work teams to accomplish their goals and are becoming significantly more diverse. This study was an attempt to combine these emerging trends and further investigate team diversity. The study was conducted among 62 software development teams from 21 different IT organisations. The results of the study demonstrated that the relationship between team diversity and work team outcomes is moderated by the levels of interdependence among team members; the team tenure i.e. the time team members spent working together, and the project/task type.